Preparation for Objective Structured Clinical Examination: A student perspective. Issue 6 (June 2019) - Brown, James
Aim: The aim of this study was to explore how student Operating Department Practitioners prepared for an Objective Structured Clinical Examination. Methods: A mixed methods design was used; questionnaires were used to gather data from a group of student Operating Department Practitioners on their Objective Structured Clinical Examination experience. Results: The study found coping with anxiety and the level of information students receive are important issues in preparing for Objective Structured Clinical Examinations. Discussion: Whilst preparation with the manikin is important, it may not be enough to fully prepare students for an Objective Structured Clinical Examination. Students also need to be given sufficient information so they fully understand the competencies they will be assessed against and receive support to cope with anxiety during the Objective Structured Clinical Examination. Conclusion: Further research is needed to identify mechanisms for coping with anxiety and stress in Objective Structured Clinical Examinations.